Assessment of iodine and mercury status of Icelandic adolescent girls - Bryndís Elfa Gunnarsdóttir 1977- (2008)
Iceland has in the past been known for its high iodine status due to high fish consumption. Fish together with milk and other dairy products are the main sources of iodine in the Icelandic diet. In recent years fish intake has decreased, especially among young people. In addition to being a good source of iodine other health benefits of fish intake have been established. Mercury intake is however one of the risks associated with fish intake. The aim of this thesis was to assess the iodine status of Icelandic adolescent girls and to gather information on intake of fish and milk consumption. Mercury status was additionally assessed. A random sample of 350 Icelandic adolescent girls born in the years 1987-1992 was selected by Statistics Iceland. Of the original sample 145 accepted to participate and 112 completed the study. Two Food Frequency Questionnaires (FFQ) were used to evaluate food consumption. A blood sample was taken to measure Thyroid-stimulating hormone (TSH) and mercury concentration, and a urine sample to measure iodine and creatinine concentration. The mean urinary iodine concentration was found to be 186μg/l (SD 145) and the median 140μg/l. When iodine concentration was adjusted for urinary creatinine the mean urinary iodine concentration was 126μg/g (SD 99) and the median 103μg/g. 10-15% of the subjects had iodine concentration below 50μg/l and 24-31% had iodine concentration below 100μg/l. Milk and dairy products were the main source of iodine, providing 43% of the iodine in the diet followed by fish providing 24%. A positive association was seen between milk consumption and iodine concentration (r=0.275 and p=0.003). The average intake of fish was less than 15g/day. Fish intake was not directly related to urinary iodine concentration. The mean mercury concentration in blood was found to be 1.47μg/l (SD 1.05) and the median 1.32μg/l. A positive correlation was found between fish consumption and mercury concentration in blood (r=0.416 and p>0.001). However the mercury concentration was far below ...